HUBUNGAN SENAM OSTEROPOROSIS TERHADAP EMANDIRIAN LANSIA DI PERKUMPULAN SENAM PONDOK MELATI KOTA BEKASI - Yunita Amelia (2013)
Elderly is a person who reaches the age of 60 years and over. Aging process has a big impact for elderly. As they grows up, people will encounter some physical degradation within their body. this physical degradation can influence their daily activity living. In addition, the other problem dominating in life of elderly is their health problem. The major health problem that oftenly concerned by elderly, and caused by degenerative disease, one of them is bone mass reduction that can change the structure of the bone or often called in term osteoporosis. In Indonesia, the number of people with osteoporosis alone could not be ascertained. Existing studies report that people with osteoporosis in Indonesia is approximately 10% in 2005. One conducted in order to have a healthy body, self and prevent osteoporosis for example by doing sports like gymnastics osteoporosis. Gymnastics is one of the sports that basically easy movement so easily followed by the elderly. The purpose of this study to determine the relationship to osteoporosis gymnastics association gymnastics independence of the elderly in Pondok Melati Bekasi. This study use a cross sectional design methodology. Sample amounted to 41 seniors. Data provided by using questionaire in sample, and the use of saturated samples. Chi square alpha 5 % used to analyze the data. Test results showed there are relation between frequency gymnastics (p=0,011) on ADL and (p=0,024) on IADL against elderly people independence. No relationship between education (p=0.147) on ADL, (p=0.075) on IADL and type of venereal (p=1.000) on ADL, (p=0.701) on IADL with elderly people independence.